(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In both the urban and rural areas of India, the education system is still in its infancy. The middaymeal is a programme developed to encourage students to continue their study. To combat pandemic, thegovernment implemented a countrywide lockdown on March 25, 2020., which has had a significantinfluence on schooling. After China, India has the world’s second-largest educational system. Asaccording UNESCO, 63 million instructors in 165 countries were impacted. A number of 1.3 billionstudents were unable to attend the school or institutions throughout the globe, with nearly 320 millionstudents in India alone. It has shifted the old educational system to a paradigm based on educationaltechnology, in which instruction and evaluations are done online. Pandemic has both beneficial and badeffects on the Indian educational system. The purpose of this study is to examine the impactof pandemic on the Indian educational system.